Analysis of Using Social Media to Increase Income of Micro and Small Business In South Tangerang - Sri Retnaning Sampurnaningsih; Jeni Andriani; Retno Wulansari (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
In the current digital and new normal era, social media was being an important source of information, for entrepreneur, especially UMK (Micro and Small Business) players in marketing their products by optimizing the use of technology. The lack of income for micro and small business entrepreneur, because the majority of them still market their products in traditional and conventional ways. Knowledge, technological stuttering, internet access and technological devices were separately obstacles for MSE actors, but not a few of them have started using technology in product marketing, especially with the Covid-19 pandemic which has begun to spread in the world and Indonesia, especially those whose impact has been felt since February 2020, which has encouraged business actors to be able to use technology, especially social media to keep their product marketing ongoing. This study aims to analyze the use of social media with the use of applications of GoFood and/or GrabFood to increase income for MSEs in South Tangerang. The research method used in this research was a case study with a qualitative descriptive method, the data source in this study uses primary data from 122 respondents of MSEs (Micro and Small Enterprises) in South Tangerang based on purposive sampling, namely MSEs actors who market their products online. at least the last three months used applications on social media, such as applications of Gofood and/or Grabfood. The results of the study show that 61.5 percent of MSE respondents use application services for food delivery, both Gofood and GrabFood. From the above application users, the most widely used is GrabFood (51.65). There was an increase in income after using social media such as the Gofood and Grabfood delivery applications (82%).